Comparing Emotion Recognition Skills among Children with and without Jailed Parents - Hindt, Lauren A.; Davis, Laurel; Schubert, Erin C.; Poehlmann-Tynan, Julie; Shlafer, Rebecca J. (Frontiers in Psychology, 2016)
Approximately five million children in the United States have experienced a co-resident parent’s incarceration in jail or prison. Parental incarceration is associated with multiple risk factors for maladjustment, which may contribute to the increased likelihood of behavioral problems in this population. Few studies have examined early predictors of maladjustment among children with incarcerated parents, limiting scholars’ understanding about potential points for prevention and intervention. Emotion recognition skills may play a role in the development of maladjustment and may be amenable to intervention. The current study examined whether emotion recognition skills differed between 3- to 8-year-old children with and without jailed parents. We hypothesized that children with jailed parents would have a negative bias in processing emotions and less accuracy compared to children without incarcerated parents. Data were drawn from 128 families, including 75 children (53.3% male, M = 5.37 years) with jailed parents and 53 children (39.6% male, M = 5.02 years) without jailed parents. Caregivers in both samples provided demographic information. Children performed an emotion recognition task in which they were asked to produce a label for photos expressing six different emotions (i.e., happy, surprised, neutral, sad, angry, and fearful). For scoring, the number of positive and negative labels were totaled; the number of negative labels provided for neutral and positive stimuli were totaled (measuring negative bias/overextension of negative labels); and valence accuracy (i.e., positive, negative, and neutral) and label accuracy were calculated. Results indicated a main effect of parental incarceration on the number of positive labels provided; children with jailed parents presented significantly fewer positive emotions than the comparison group. There was also a main effect of parental incarceration on negative bias (the overextension of negative labels); children with jailed parents had a negative bias compared to children without jailed parents. However, these findings did not hold when controlling for child age, race/ethnicity, receipt of special education services, and caregiver education. The results provide some evidence for the effect of the context of parental incarceration in the development of negative emotion recognition biases. Limitations and implications for future research and interventions are discussed.